OPTIMALISASI PRODUKSI ENZIM KITINASE PADA ISOLAT JAMUR KITINOLITIK DARI SAMPEL TANAH RIZOSFER - Eka Corneliyawati; Massora; Khikmah; As’ad Syamsul Arifin (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
The rhizosphere is the zone of soil surrounding a plant root where plant roots, soil and the soil biota interact with each other. Chitinolytic fungi has been effectively used in biological control agens. The chitinase activity causes lysis of the fungi cell wall pathogen. The aim of the research was to find optimization of activity chitinase enzyme from rhizosphere soil was conducted in vitro. Optimal growth chitinase production for TKR3 fungi isolate were concentration of chitin 0,2% (b/v), pH 5,5, temperature 30ºC, agitation 150 rpm and incubation time at four days. The optimum yield of chitinase production is influenced by fungal species and environmental conditions.